Assessment of Key Imperatives for Enhancing Precast Adoptability in Egypt - Sameh, Mostafa (AUC Knowledge Fountain, 2021)
Precast Concrete’s modular application concept is a major construction method that has been used historically seen in various shapes, forms, and with a wide range of constituents. Examples include Ancient Egypt and China among several impressive structures in old civilizations. The major advantages of precast concrete lie in its adaptability, resilience, and versatility which makes precast concrete one of the most agile building materials. Precast concrete as we know it today has been introduced to our markets over the past several decades. Having similar advantages to that of old precast building methods, the road has been paved for wider use of modern precast concrete in the construction industry. However, this use has been somewhat limited in Egypt despite the booming and ever-growing construction industry. As such, questions arise as to why precast has not sufficiently penetrated the Egyptian market and what could be the barriers or disadvantages that limit its use. Answering those questions could illuminate a protocol guide for precast concrete to be more commonly used within Egypt. The main objective of this study is to assess the status of precast concrete in Egypt in an attempt to pinpoint both the advantages and the disadvantages as well as the barriers associated with its use. To meet this objective, aspects related to precast concrete are discussed including its adaptability to the ever-booming Egyptian construction industry, its capabilities, as well as the value-added that it can render. The Egyptian market is taken as an example of an emerging market where a full set of material products are considered. To cope with recent advances, modern methods of using precast concrete are taken into consideration with increased aesthetic and performance capabilities are covered by this work. Data analysis, as well as surveys, are used to adequately incorporate actual market conditions and concerns into the findings of this work. Sites were also visited where accessible while taking face-to-face surveys and alignment interviews. The study rendered a summary of major trends of precast concrete in the Egyptian construction industry with an analysis of their impact on its market strength and values-added. Recommendations are further provided for the concrete society and the construction industry by in large towards better utilization of precast concrete in Egypt.